Generic and Subtribal relationShipS in neotropical cymbidieae (orchidaceae) baSed on matK/ycf1 plaStid data - Whitten, W Mark (Universidad de Costa Rica, 2014)
Relationships among all subtribes of Neotropical Cymbidieae (Orchidaceae) were estimated using combined matK/ycf1 plastid sequence data for 289 taxa. The matrix was analyzed using RAxML. Bootstrap (BS) analyses yield 100% BS support for all subtribes except Stanhopeinae (87%). Generic relationships within subtribes are highly resolved and are generally congruent with those presented in previous studies and as summarized in Genera Orchidacearum. Relationships among subtribes are largely unresolved. The Szlachetko generic classification of Maxillariinae is not supported. A new combination is made for Maxillaria cacaoensis J.T.Atwood in Camaridium.